Rethinking Autoimmunity in Regenerative Medicine: A Review of Diabetic Treatment Options - Benjamin Borokhovsky (Recent Developments in Medicine and Medical Research Vol. 14, 2021)
Type I Diabetes Mellitus (T1DM) is an autoimmune pathology that occurs when auto-reactive cytotoxic CD8+ T-cells destroy native pancreatic insulin producing \(β\) islet of Langerhans cells reducing endogenous insulin levels. The objective of this chapter is to provide the reader with a summary of recent advances that provide new perspective on the future of autoimmunity as it relates to regenerative medicine and diabetes. Stem cells were previously thought to play a pivotal role in the re-population of diseased pancreatic \(β\) cells but recent studies now indicate that the regenerative capability of these insulin producing cells remains intact even years after initial diagnosis. Thus, emphasis shifted from investigating re-population techniques using splenic or exogenous grafting stem cells to abating the initial autoimmune process to prevent further islet cell destruction by auto-reactive cytotoxic CD8+ T-cells. Tumor necrosis factor alpha (TNF- \(α\)) is believed to play a role in therapeutic options for diabetics, as there is reason to believe that TNF-\(α\) is capable of inducing apoptosis in selectively autoreactive CD8+ T-cells. Furthermore, the next generation of ultrasensitive c-peptide assays shed light on the true functional status of \(β\) islet cells and conclude that the decline in function occurs over decades and not months as was previously thought. Trials involving using mycobacterial adjuvants have shown that not only mice, but also diabetics remain euglycemic for a long period after administration. All these concepts and discoveries pave the way for future clinical trials and the discovery of more curative diabetic treatment options.